Relationship Between Blood Pressure Values and High-Density Lipoprotein (HDL) Levels in Hypertensive Patients at Balaraja Hospital - Novia Nur Andini; Nining Kurniati; Yuliani, Raden Adjeng Dewi Maria; Nadia Guntari; Priscila Santos (Journal of Noncommunicable Diseases Prevention and Control, 2025)
Blood pressure and high-density lipoprotein (HDL) levels are two major indicators used in the assessment of cardiovascular health. Both play important roles in the risk of heart disease and stroke. High blood pressure, both systolic and diastolic, is a major risk factor for various cardiovascular diseases. Meanwhile, HDL levels are often considered "good cholesterol" because of their ability to transport cholesterol from the arteries to the liver, where it can be removed from the body. This study aimed to determine the relationship between blood pressure values and high-density lipoprotein levels in hypertensive patients at Balaraja Hospital. This study used a cross-sectional design. The sample consisted of 19 patients who met the inclusion criteria. The examination method used was Cholesterol Oxidase Para Amino Penazon (CHOD-PAP). The normality test results showed a p-value of p = 0.101 for HDL levels, p = 0.006 for systolic blood pressure, and p = 0.018 for diastolic blood pressure, indicating that HDL levels could be considered normally distributed, whereas blood pressure was not normally distributed. Therefore, further analysis used a correlation test. The results of Spearman rank correlation showed a significance value of p = 0.062 for systolic blood pressure and p = 0.190 for diastolic blood pressure, indicating that there was no significant relationship between HDL levels and blood pressure, with a very weak correlation for systolic blood pressure (r = 0.010) and diastolic blood pressure (r = 0.190). The conclusion of this study was that there was no significant relationship between blood pressure and HDL levels in hypertensive patients at Balaraja Hospital.